Characterizing the wrinkling behavior of woven engineering fabrics with local non-uniformity. (March 2019) - Moezzi, Meysam; Yekrang, Javad; Khodadad, Ali; Hatami, Mehdi
Abstract: Experimental investigation of the wrinkle behavior was done with some simplifying assumptions such as material uniformity. However, non-uniformity as a source of error is often observed at the geometrical or mechanical properties of the local areas. This paper focused on the effect of the local variation of the woven engineering fabrics on the shear and wrinkle behavior of it through the uniaxial bias extension tests. UV exposure was used to apply the local degradation in the material. The influence of controlled non-uniformity with four different levels on the shear and wrinkle behavior of the fabric was experimentally determined using the image processing method. Experimental results showed that the shear and wrinkle behavior was unique due to the source of non-uniformity and the virgin material behavior. FT-IR, microscopic and TGA analyses were also performed to analyze the molecular, morphological and thermal characteristics of the samples and confirm the experimental results.